THE EFFECT OF AWARENESS KNOWLEDGE OF TECHNOLOGY-BASED TAX, AND TAX SANCTIONS AGAINST MSME TAXPAYER COMPLIANCE - Andrew, Richard; Lusy, Lusy; Mastan, Stanislaus Adnanto; Septian, Winda (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The highest source of state revenue comes from tax revenue,according to the DGT (2023) explaining that the source of state tax revenue is IDR 162 trillion. This tax source is used for the construction of facilities for communities throughout Indonesia. A taxpayer is required to always comply both in terms of reporting property through a notification letter (SPT) and tax payments each year. The object of research in this study is all MSME taxpayers registered in Sidoarjo and Surabaya.The selection of places is because East Java province has the third largest number of MSMEs after West Java and Central Java with data of 1,153,576 in 2022. Sidoarjo is one of the districts with the largest number of MSMEs in Indonesia at 206,000, while Surabaya is the capital of East Java province and has a total of 60,000 MSMEs in 2021. Surabaya and Sidoarjo are also the two largest industrial sites in East Java compared to other regions. Sampling techniques in this study using purposive sampling. This type of research is quantitative research with questionnaires through Google Form with a Likert scale of 1-5.The purpose of this study is to analyze and test the effect of taxpayer awareness, technology-based tax knowledge and tax sanctions on MSME taxpayer compliance. The specific purpose of this study is to see whether the level of compliance of an MSME taxpayer is maintained in the midst of extraordinary technological developments in the Industrial Revolution 5.0. The urgency of this study is that if MSME taxpayers have a level of awareness, science and technology-based knowledge, different tax sanctions and different taxpayer compliance, the special specifications in this study, focus more on the theme of sustainable tax research in terms of level of awareness, knowledge and tax sanctions. The stages of this research include: (1) Preparing questionnaires related to factors that affect awareness, technology-based knowledge, tax sanctions on MSME taxpayer compliance (2) Preparing research proposals; (3) distributing questionnaires for MSME taxpayers in Sidoarjo and Surabaya; (4) collecting questionnaires; (5) processing data; (6) discussing data that has been processed; (7) preparing publication outputs; (8) making a final report. The urgency of this research is related to the research model that examines the variables of awareness, technology-based knowledge, tax sanctions and compliance of MSME taxpayers, especially from the questionnaire items distributed. Keywords: Awareness knowledge, science and Technology, Tax sanctions, taxpayer compliance, MSMEs